Analisis Saringan Terhadap Hasil Penepungan Rumput Laut dengan Mesin Disc Mill dan Penggerak Motor Bensin dalam Waktu Tertentu - M. Zakki Hilmi Mubarok; Althesa Androva; Aan Burhanudin (CV. IRA PUBLISHING, 2025)
This study analyzes the effect of sieve size and operating parameters on seaweed grinding performance using a Disc Mill machine powered by a gasoline engine. The experiments were conducted using a constant initial material mass of 125 g with variations in sieve size (0.3 mm, 0.5 mm, and 0.8 mm) and rotational speed ranging from 2000 to 2400 RPM. The results indicate that sieve size significantly influences the amount and quality of flour produced. The highest flour yield of 79 g was obtained using a 0.8 mm sieve at 2200 RPM, while the lowest yield of 44 g was produced using a 0.5 mm sieve at 2400 RPM. Smaller sieve sizes improved particle fineness but reduced flour yield due to longer particle retention within the grinding chamber. The Disc Mill machine with a gasoline engine drive demonstrated good operational flexibility, particularly in areas without electricity access. Overall, the performance of the Disc Mill machine strongly depends on the appropriate selection of sieve size and operating parameters. These findings highlight the potential of Disc Mill technology to improve efficiency and product quality in seaweed flour processing.